PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI GERAK BENDA DI MTSN 3 ACEH UTARA TAHUN AJARAN 2019/2020 - Ruhul Masyithah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2020)
The research aims to determine an increase in student learning outcomes and to describe the activities of teachers and students in the application of the STAD (Student Teams Achievement Division) cooperative learning model on straight motion material in MTSN 3 Aceh Utara Academic Year 2019/2020, 2. To describe student responses to application of the STAD (Student Teams Achievement Division) cooperative learning model on straight motion material in MTs.N 3 of North Aceh for the 2019/2020 academic year. This research with a qualitative approach. Thus the sample of this study amounted to 24 people. Data was collected by means of ptk stages. Based on the results of research data analysis. Student learning outcomes using the STAD cooperative learning model increased through the average acquisition of 56.45 in the first cycle, an increase of 8.33 then 63.96 in the second cycle. 2. The activities of teachers and students have increased in the teaching and learning process using the cooperative learning model type Student Teams Achievement Division (STAD), in science subjects on object motion material for class VIII MTsN 3 Aceh Utara students, shown well in cycle 1 teacher activity with good category. There was an increase in cycle 2, namely in the good category. Furthermore, student activity in cycle 1 was categorized as good. and there was an increase in cycle 2 in the very good category.